Solar energy management system with supercapacitors for rural application - Romli, Muhammad Izuan Fahmi (2018)
Growing energy demands are expected to exceed the supply from current energy resources. Therefore, renewable energy and energy management systems will become more crucial for increasing supply and efficiency of energy usage. The novelty of this research is an energy management system (EMS) based on fuzzy logic for a solar house to ensure the maximum utilisation of renewable sources, protect components from being damaged due to overloading, and manage energy storage devices to increase stability in the power system. There is no published analysis of hybrid energy storage between battery and supercapacitor using fuzzy logic as EMS. The energy management system is implemented in a solar cabin system developed by IBC Solar to mimic a typical rural house. The solar cabin is equipped with solar photovoltaic panels, solar charger, battery and inverter. Supercapacitors and a custom made DC to DC converter were added to the system to support the batteries during high current load demand and manage energy flow. Three sets of experiments were conducted in the solar cabin system with the new energy management system. Power consumption usage of a typical rural household was studied to create two load profiles that were used as load for the experiments. The results show an efficiency of 95.9% by using the new energy management system and supercapacitors to the solar cabin, which is higher than recent research (95.2% and 84.4%). The result is on par with the Malaysian and International Standard in energy efficiency of around 95%. The energy management system controlled the charging and discharging of the battery and supercapacitor using fuzzy logic. The novelty of this thesis is use of supercapacitors to reduce stress on the battery and an energy management system to control and manage the system for efficient energy usage.